When keystroke meets password: Attacks and defenses - LIU, Ximing (Institutional Knowledge at Singapore Management University, 2019)
Password is a prevalent means used for user authentication in pervasive computing environments since it is simple to be deployed and convenient to use. However, the use of password has intrinsic problems due to the involvement of keystroke. Keystroke behaviors may emit various side-channel information, including timing, acoustic, and visual information, which can be easily collected by an adversary and leveraged for the keystroke inference. On the other hand, those keystroke-related information can also be used to protect a user's credentials via two-factor authentication and biometrics authentication schemes. This dissertation focuses on investigating the PIN inference due to the side-channel information disclosure and exploring the design of a new two-factor authentication system. The first work in this dissertation proposes a user-independent inter-keystroke timing attack on PINs. Our attack method is based on an inter-keystroke timing dictionary built from a human cognitive model whose parameters can be determined by a small amount of training data on any users. Our attacks can thus be potentially launched in a large scale in real-world settings. We investigate inter-keystroke timing attacks in different online attack settings and evaluate their performance on PINs at different strength levels. Our experimental results show that the proposed attack performs significantly better than random guessing attacks. We further demonstrate that our attacks pose a serious threat to real-world applications and propose various ways to mitigate the threat. We then propose a more accurate and practical PIN attack based on ultrasound, named UltraPIN, in the second work. It can be launched from commodity smartphones. As a target user enters a PIN on a PIN-based user authentication system, an attacker may use UltraPIN to infer the PIN from a short distance without a line of sight. In this process, UltraPIN leverages on smartphone speakers to issue human-inaudible ultrasound signals and uses smartphone microphones to keep recording acoustic signals. It applies a series of signal processing techniques to extract high-quality feature vectors from low-energy and high-noise signals. Taking the extracted feature vectors as input, UltraPIN applies a combination of machine learning models to classify finger movement patterns during PIN entry, and generates a ranked list of highly possible PINs as result. Rigorous experiments show that UltraPIN is highly effective in PIN inference and robust to different attacking settings. Keystroke timing information and keystroke typing sounds can also be used to protect users' accounts. In the third work, we propose Typing-Proof, a usable, secure and low-cost two-factor authentication mechanism. Typing-Proof is similar to software token based 2FA in a sense that it uses password as the first factor and uses a registered phone to prove the second factor. During the second-factor authentication procedure, it requires a user to type any random code on a login computer and authenticates the user by comparing the keystroke timing sequence of the random code recorded by the login computer with the sounds of typing random code recorded by the user's registered phone. Typing-Proof achieves good performance in most settings and requires zero user-phone interaction in most cases. It is secure and immune to the existing attacks to recent 2FA mechanisms. In addition, Typing-Proof enables significant cost savings for both service providers and users. This dissertation makes contributions to understanding the potential risk of side-channel information leaked by keystroke behaviors and designing a secure, usable and low-cost two-factor authentication systems. On the one hand, our proposed side-channel attacks make use of human cognitive model and ultrasound, which provides useful insights into the field of combining cognitive psychology and Doppler effect with human behavior related insecurity. On the other hand, our proposed two-factor authentication system eliminates the user-phone interaction in most cases and can effectively defend against the existing attacks to recent 2FA mechanisms.